ENHANCING SOCIAL ENTREPRENEURSHIP AWARENESS AMONG CHURCH ORGANIZATIONS: A LITERATURE REVIEW - Bukidz, Danny Philipe (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research explores the emerging awareness of social entrepreneurship within religious organizations, focusing particularly on the role of church communities in fostering social entrepreneurial initiatives. Drawing on a comprehensive literature review, the study examines the interplay of individual, organizational, and societal factors influencing social entrepreneurship awareness within church organizations. Key findings reveal the significance of personal attributes such as self-efficacy and emotional intelligence, educational support mechanisms including mentorship and networking, and broader societal and economic contexts in shaping individuals' inclination towards social entrepreneurship within church settings. Additionally, the study highlights strategies for enhancing social entrepreneurship awareness at church organizations, ranging from education and training programs to community engagement projects and collaboration with external stakeholders. Implications for practice and policy underscore the importance of creating a supportive environment for social entrepreneurship within churches and advocate for further research to evaluate intervention effectiveness and address ethical considerations. Overall, this research contributes to a better understanding of social entrepreneurship awareness within religious organizations and offers practical insights for fostering a culture of social innovation and community development within church communities.